2021
DOI: 10.1021/acs.langmuir.1c01569
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Adhesion and Phase Change Behaviors of Sulfur Droplets on the Superhydrophobic Surface and Its Application in the Granulation Process

Abstract: Traditional sulfur granulation process is often accompanied by high dust and mechanical friction, which are dangerous and harmful to the environment. In this work, the application of the superhydrophobic surface to sulfur granulation is expected to solve the above problem. Two superhydrophobic metal sheets were prepared, and the rolling angles of the two samples are both less than 10°. The contact angles of liquid sulfur are 152.7 ± 0.5 and 151.3 ± 0.1°, respectively. The adhesion rates of both samples are les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The marbles are prone to agglomeration and breakage in collision and transportation, which greatly reduces the efficiency of the preparation of liquid/melt marbles. Particularly, for melt marbles such as urea and sulfur, the increased viscosity and density of the materials often result in reduced elasticity and sphericity of the marbles. , Consequently, this further hampers their overall performance and effectiveness in applications. At the same time, the phase change process involved in preparing and transporting the melt marbles makes it more difficult to control the granulation process.…”
Section: Introductionmentioning
confidence: 99%
“…The marbles are prone to agglomeration and breakage in collision and transportation, which greatly reduces the efficiency of the preparation of liquid/melt marbles. Particularly, for melt marbles such as urea and sulfur, the increased viscosity and density of the materials often result in reduced elasticity and sphericity of the marbles. , Consequently, this further hampers their overall performance and effectiveness in applications. At the same time, the phase change process involved in preparing and transporting the melt marbles makes it more difficult to control the granulation process.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Liu et al showed that the sulfur granulation process is not only environmentally friendly, but also results in a uniform particle size distribution of the raw material. 13 Rapeseed is the most widely grown oilseed crop in China, accounting for more than 40% of the country's total oilseed crop area. It is estimated that about 20 million tonnes of rapeseed straw is produced annually as an agricultural by-product.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 12 used granulation and cold press sintering to prepare copper‐based friction materials with better wear resistance than ungranulated ones. The results of Liu et al showed that the sulfur granulation process is not only environmentally friendly, but also results in a uniform particle size distribution of the raw material 13 …”
Section: Introductionmentioning
confidence: 99%